Gastric Mucinous Cancer Histology: Clinicopathological Characteristics and Prognostic Value - Chen Jian-Hui; Cai Shi-Rong; Wu Hui; Xu Jian-bo; Wu Kai-Ming; Chen Si-le; Yu-Long He (Gastroenterology Research and Practice)
MC tended toward worse tumor biological behavior and long-term survival outcome compared to WMDC. Moreover, MC also showed worse clinicopathological features and survival outcome in some selected patients. For these reasons, MC should be deemed as a special histological type of gastric cancer with worse clinicopathological features and survival outcome.